Factors Affecting Tourism Destination Competitiveness in Vietnam - LE, Manh Hung; TA, Van Loi; HA, Dieu Linh; LE, Anh Duc; VU, Tri Tuan (Journal of Tourism Management Research, 2022)
The study's objective was to explore and measure the impact of factors affecting tourism destination competitiveness in Vietnam. Participants included 192 tourists in Hanoi city and neighboring provinces in the period from October 2021 to April 2022. Based on the 192 valid responses from the questionnaire survey method, the correlations between the variables were analyzed and the hypotheses verified. To study the relationships among the latent variables with reliable tools (SmartPLS 3.0 software), the study applied the partial least squares approach to structural equation modeling (PLS-SEM). The results identified the following factors that affect tourism destination competitiveness in Vietnam: Environmental quality is the most influential factor; Tourism infrastructure and Tourist satisfaction have the second-strongest influence on tourist destination competitiveness; Historical and sociocultural perspectives and Human resources also affect tourist destination competitiveness. The study provides empirical evidence and explains the factors that affect tourist destination competitiveness. Finally, several recommendations are put forward to enhance tourism destination competitiveness in Vietnam.